2019
DOI: 10.21608/zjar.2019.33384
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Genetic Diversity in Sesame

Abstract: The present investigation was carried out to identify eleven sesame lines during two successive seasons (2016 and 2017). The phenotypic variance (σ 2 ᵖ) was greater than the corresponding variance for all studied traits except capsule thickness. The genotypic variance and phenotypic variance values for number of capsules/plant and oil yield/fad., were high over the two years. High broad-sense heritability accompanied with high genetic advance was recorded for No. of branches/ plant, seed yield/plant and seed y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…This indicated that an increased influence of environment on these traits and thus the selection procedures involving progeny testing are recommended for these traits. Similar results were found by Mourad et al (2019), who recorded that the expected genetic advance ranged from 2.28% for standard germination to 22.31% for seedling dry weight. PCV: Phenotypic coefficient of variability, GCV: Genotypic coefficient of variability, h 2 b : Broadsense heritability, GA 5%: Genetic advance, GAM% of means: Genetic advance as percent of the mean.…”
Section: Seed Quality: Germination Traitssupporting
confidence: 88%
“…This indicated that an increased influence of environment on these traits and thus the selection procedures involving progeny testing are recommended for these traits. Similar results were found by Mourad et al (2019), who recorded that the expected genetic advance ranged from 2.28% for standard germination to 22.31% for seedling dry weight. PCV: Phenotypic coefficient of variability, GCV: Genotypic coefficient of variability, h 2 b : Broadsense heritability, GA 5%: Genetic advance, GAM% of means: Genetic advance as percent of the mean.…”
Section: Seed Quality: Germination Traitssupporting
confidence: 88%